2017
DOI: 10.1111/jori.12218
|View full text |Cite
|
Sign up to set email alerts
|

RISK GOVERNANCEINTHE INSURANCE SECTOR—DETERMINANTSAND CONSEQUENCESINAN INTERNATIONAL SAMPLE

Abstract: We analyze the relation between risk governance, risk, and performance measures for a global sample of 107 insurance companies from 2004 to 2012. Our risk governance index (RGI) covers several Solvency II provisions and includes the existence of chief risk officer on the executive committee, risk committee characteristics, and board industry experience. We find that in the crisis period 2008–2009, firms with a higher RGI generally have lower expected default frequency. We conclude that during noncrisis years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Ellul and Yerramilli's (2013) risk management index incorporates not just measures of CRO status but also indicators of board risk committee effectiveness, confirming the relevance of effective governance for improved US bank performance during the crisis. Magee et al (2019) established similar findings supporting similar governance structures in an international sample of insurance companies. Not only did they deliver superior crisis outcomes, but also an advantage in the post-crisis years.…”
Section: Related Literaturesupporting
confidence: 75%
“…Ellul and Yerramilli's (2013) risk management index incorporates not just measures of CRO status but also indicators of board risk committee effectiveness, confirming the relevance of effective governance for improved US bank performance during the crisis. Magee et al (2019) established similar findings supporting similar governance structures in an international sample of insurance companies. Not only did they deliver superior crisis outcomes, but also an advantage in the post-crisis years.…”
Section: Related Literaturesupporting
confidence: 75%
“…The study is related to the literature examining the role of directors and senior executives in risk management. Several studies have now demonstrated the favourable outcomes associated with risk governance in financial institutions (Ellul and Yerramilli, 2013;Aebi et al, 2012;Magee et al, 2017). Related to this is a literature on board diversity that sheds light on the characteristics of directors in relation to risk-taking (Berger et al, 2014;Adams and Ragunathan, 2015;Sila et al, 2016).…”
Section: Introductionmentioning
confidence: 97%